(untitled) (Journal of the College of Basic Education, 2022)
The housing sector is of great economic and social importance, as it is one of the most important sectors on which countries ’policies are based because of the political stability and economic prosperity that it provides. Therefore, the need to establish residential complexes that suit the increase in population numbers and ensure a life of well-being and prosperity in them, that these complexes require the provision of The correct technical framework that organizes it and sets standards and laws for its establishment to provide a suitable housing environment in line with international laws and standards that are adopted in other countries, to ensure the vitality and comfort of the population and bring it closer to the state of sustainability, so the presence of indicators that serve this purpose is required, and among the most important of these indicators is urbanism, As the research focuses on the problem of what are the indicators of the residential urban environment for the study area, and are they planned according to appropriate urban indicators? What is the extent of the residents’ satisfaction with it ?,The aim of this study is to determine the most important indicators of the appropriate residential environment in the studied area from the urban point of view, in terms of housing unit designs and activities within the urban community as well as evaluating the services provided to residents, and the study is based on the assumption that the urban elements have been taken Considering the consideration when planning the study area and it was in accordance with appropriate urban indicators and it won the satisfaction of the residents. Therefore, the study relied on the descriptive and analytical approach to the data and on the experiences of some countries in achieving adequate housing, including personal interviews with officials and residents of the area, as well as relying on research and studies. The approved and published process, and taking the opinion of the residents using the questionnaire form specifically for that which was determined by taking the opinion of a group of experts to find out the most important urban indicators and to know the extent of the residents’ satisfaction with them. A set of conclusions were reached, the most important of which is most of the urban standards for the residential environment of the study area, which are identical in terms of design and implementation to the national standards, except for some neglect in green areas, children’s play areas and parks. Overtaking them. And setting up a strict mechanism for approving the general and detailed plan by reliable consulting offices before starting the implementation, and obliging the companies implementing the residential complexes to implement all uses as planned.